Green criminology: crime, justice and the environment - Lynch, Michael J. (University of California Press, 2017)
Introduction : green criminology and political economy -- The state of green criminology -- Pollution crimes -- Withdrawal crimes -- Crimes of ecological additions and illness -- Crimes of overproduction and overconsumption -- Toxic towns and studies of ecologically devastated communities -- Wildlife trafficking, smuggling, and poaching -- Environmental justice and green criminology -- Environmental law and the treadmill of environmental law -- Environmental social movements and environmental non-government organizations -- Connecting the dots : explaining green crimes